Pengembangan Media Pembelajaran Berbasis Benda Konkret untuk Meningkatkan HOTS Peserta Didik Kelas IV Sekolah Dasar - Ritonga, Adelia Priscila; Anas, Nirwana (Universitas Negeri Padang, 2024)
The low high-level thinking skills (HOTS) of fourth-grade students in science subjects, especially in the ability to analyze and create. The main objective of this study is to improve the HOTS of fourth-grade students by developing learning media based on concrete objects. The research conducted in this study uses the Research and Development (R&D) method by applying the 4D development model, namely Define, Design, Develop and Disseminate. Data collection techniques used were questionnaires, interviews, and tests. The study subjects were 32 fourth-grade students of SDN 09 Bilah Hilir. Data analysis used validity, practicality, and effectiveness tests. Media and material experts assessed the media created as very valid (86% and 90%, respectively). Both teachers and students scored in the